2011
DOI: 10.3354/cr00957
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-meteorological trends in the upper Indus River basin in Pakistan

Abstract: We examined trends in several hydro-meteorological variables in the upper Indus River basin (UIRB) in Pakistan. To represent the diversity of hydro-meteorological conditions in the basin, mean monthly data from 20 meteorological and 8 hydrometric stations were analyzed for detection of trends using the non-parametric Mann-Kendall test in combination with the trend-free pre-whitening approach for correcting time series data sets for serial correlation. Sen's slope method, a non-parametric alternative for estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
175
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(205 citation statements)
references
References 41 publications
(47 reference statements)
24
175
6
Order By: Relevance
“…A significant falling trend of the end-of-summer regional snow line altitude for the eastern Karakoram over the period 2000-2012 also indicates a positive change in the high-altitude frozen water resources therein [25]. For other main cryospheric regions of the UIB, the studies consistently report and support cooling phenomenon [4,17,19,21,27,28,30,35,36,75,76]. Over the whole UIB, increasing snow cover in a recent decade [25,26] and conflict of tree-ring based paeleoclimatic Karakoram summer temperatures with the hemispheric warming for recent five centuries [23] have also been reported.…”
Section: Prevailing Hydro-cryo-climatic Changessupporting
confidence: 48%
See 1 more Smart Citation
“…A significant falling trend of the end-of-summer regional snow line altitude for the eastern Karakoram over the period 2000-2012 also indicates a positive change in the high-altitude frozen water resources therein [25]. For other main cryospheric regions of the UIB, the studies consistently report and support cooling phenomenon [4,17,19,21,27,28,30,35,36,75,76]. Over the whole UIB, increasing snow cover in a recent decade [25,26] and conflict of tree-ring based paeleoclimatic Karakoram summer temperatures with the hemispheric warming for recent five centuries [23] have also been reported.…”
Section: Prevailing Hydro-cryo-climatic Changessupporting
confidence: 48%
“…The rest observed changes that are consistent with a typical climate change signal mainly include a dominant spring warming and somewhat increase in winter precipitation [4,[17][18][19]. Nevertheless, a summer cooling phenomenon is unique for the UIB with the present-day climate models being unable to represent it even at a qualitative scale [16].…”
Section: Prevailing Hydro-cryo-climatic Changesmentioning
confidence: 99%
“…Liu et al, 2009;Liu and Chen, 2000;Qin et al, 2009;Thompson et al, 2003;Yang et al, 2011). Similar findings are reported by Shrestha et al (1999) for Nepalese Himalayas and Khattak et al (2011) in winter (Dec-Feb) Tmax for Pakistan's upper Indus River Basin.…”
Section: Strong Evidence Of Warmingsupporting
confidence: 76%
“…In the same basin, Khattak et al (2011) find spatially inconsistent and generally statistically insignificant seasonal precipitation trends during 1967-2005; however, they note more increasing than decreasing trends.…”
Section: Spatial Variability In Precipitation Trendsmentioning
confidence: 88%
“…The impact of climate change on runoff is more adverse, especially in snow-fed rivers [21][22]. Significant decreasing trends in summer and increasing trends in winter in mean monthly flow were observed at eight stream gauging stations located in the UIB [23]. The analysis of the observed annual average discharge from 2001-05 showed that the contribution of precipitation to the average annual discharge was less than that of snowmelt due to enhanced glacier melting in the UIB [10].…”
Section: Introductionmentioning
confidence: 99%